Psychologiczne wątki w encyklice Lumen fidei - Makselon, Józef (Analecta Cracoviensia, 2013)
The author is convinced, that the first Encyclical of Pope Francis Lumen Fidei (Light of Faith) offers a profound and comprehensive meditation on the role of faith in our live. The Pope writes, that the light of faith comes from God and is able to illuminate all aspects of man’s existence: it proceeds from the past, from the memory of Jesus’ life, but also comes from the future as it opens up vast horizons.In the present article the phenomenon of light and dynamics of faith are analysed from the psychological point of view.